2016
DOI: 10.30707/jste51.1hoffman
|View full text |Cite
|
Sign up to set email alerts
|

What STEM Teachers Need to Know and Do for English Language Learners (ELLs): Using Literacy to Learn

Abstract: A growing concern for STEM teachers is the responsibility of having students who do not speak English proficiently in their content area classrooms. This paper gives a background of how STEM literacy and English language learner (ELL) literacy can be used productively together as well as strategies for STEM teachers to help all students learn. Strategies for ELL literacy are good strategies for all students. We discuss specific strategies that STEM teachers can use that benefit all students in developing acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Learning writing skills requires cognitive, sociocultural and linguistic knowledge (de Oliveira & Silva, 2016; di Gennaro, 2016). Researchers are showing great interest in implementing new approaches to teaching and assessing writing (Beiler, 2020;Hoffman & Zollman, 2016). One of these positive areas of research is to create a social cognitive model by monitoring the performance of skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Learning writing skills requires cognitive, sociocultural and linguistic knowledge (de Oliveira & Silva, 2016; di Gennaro, 2016). Researchers are showing great interest in implementing new approaches to teaching and assessing writing (Beiler, 2020;Hoffman & Zollman, 2016). One of these positive areas of research is to create a social cognitive model by monitoring the performance of skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…"When we teach them in English, the next time we come back to the schools, they have forgotten everything that was taught the last time, so we had to start translating and explaining to them in Yoruba, sometimes, we turn some aspects of the lessons to then they started understanding better…" Evidence from the literature suggests that STEM teachers are sometimes concerned about the difficulty in explaining concepts to learners who are not proficient in English [38], [39]. There are a number of effective strategies to support STEM learners in this regard.…”
Section: Language Can Be a Barrier In Teaching Stemmentioning
confidence: 99%
“…Hoffman and her colleague [8] suggested that the five following strategies can be used to support language development among English language learners as well as improve their literacy: (a) build background of new concepts, (b) support students' vocabulary-building skills, (c) model how STEM vocabulary should be used, (d) encourage student language production through increasing interaction opportunities, and (e) use different grouping strategies for distinct purposes.…”
Section: Stem Education and English Language Learningmentioning
confidence: 99%
“…The second tier is the vocabulary needed for school that students might not encounter in their everyday lives or social interactions; examples might include words like seldom or classify. The third tier of vocabulary consists of academic content words which have STEM-precise definitions used in specific situations [8]". By scaffolding the lessons, teachers can gradually help students to gain deep concepts related to STEM fields.…”
Section: Stem Education and English Language Learningmentioning
confidence: 99%